Restorative Justice in Handling Corporate Crimes in Decision 187/Pid.Sus-LH/2024/PN Son - Situmorang, Otniel Raja Maruli; Firmanda, Ridho Junilham; Purba, Williem Aditya Sion (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2025)
The use of restorative justice in addressing corporate crimes, particularly in Decision Number 187/Pid. Sus-LH/2024/PN Son concerning breaches of environmental regulations by companies. In this situation, restorative justice, typically used in personal instances, can be effectively implemented by corporations that commit criminal acts. This approach explores how it influences environmental restoration and safeguards the communities that are affected. This research seeks to assess the appropriateness of utilizing the principle of restorative justice in cases of corporate crime, especially in this specific instance, and to investigate its effectiveness and legal consequences in attaining meaningful justice and promoting environmental sustainability. The research method used is normative legal research, with a statutory regulatory approach, a case approach, and a conceptual approach. This approach involves a thorough examination of court decisions, applicable laws and regulations, as well as legal theory and related literature. The findings of the research indicate that in Decision 187/Pid. Sus-LH/2024/PN Son, the implementation of restorative justice involves the requirement to rehabilitate the environment and provide compensation to impacted communities, rather than relying solely on traditional penalties like fines or incarceration for companies. This choice signifies the advancement of environmental criminal law, as it focuses on addressing actual damages instead of merely serving symbolic penalties. Restorative justice concerning environmental violations by corporations emphasizes the need to restore harmed ecological conditions rather than solely concentrating on punishment. This method promotes corporate accountability to address environmental damage and offer restitution to impacted communities. Therefore, restorative justice may serve as an alternative approach for resolving corporate criminal cases, emphasizing restoration and sustainability, accompanied by more explicit regulations and rigorous monitoring systems.